Academic Staff Strengths of Postgraduate Training Programs in Pharmacology in the USA Pre- and during Covid-19 Pandemic - A Cue for Capacity Building in Pharmacological and other Programs in Nigerian Universities (Nigerian Journal of Physiological Sciences, 2022)
Structure and function go hand in hand for program success. For the training of pharmacologists, this is also true. A component of structure is academic staff strength. We wanted to know the total academic staff strength of programs and departments in American universities that run training programs in pharmacology at post graduate level in order to inform development in Nigerian and other African academia. Through departmental and program webpages, we mined data on academic staff of departments running graduate programs leading to PhD Pharmacology in the USA. All the data were mined within 96 hours of starting the investigation in 2016 and again in 2021 and were studied using descriptive statistics. There were a total of 25 such programs listed by the American Society for Pharmacology and Experimental Therapeutics (ASPET) website. From the descriptive statistics, the programs were not identical and varied in their staff compositions by numbers. A total of 1,993 academic staff members in 2016 and 2,042 academic staff members in 2021 were serving the 25 graduate pharmacology programs collectively.  Notably more than 25% and less than 50% of the three categories of professorial cadre were non-pharmacology PhD holders. From the composite data of 2016 and 2021, mean staff per program were: 23 professors, 13 associate professors, and 15 assistant professors per program with 2 each of adjunct staff in the categories of professor, associate professors, and assistant professor.  Also composite average per program were 5 joint staff, 3 postdoctoral fellows, 4 emeritus professors, and 11 various researchers. A pattern of top heavy majority of professors was derived from both the 2016 and 2021 investigations. Post docs, miscellaneous researchers, joint staff, and emeritus professors formed a dynamic pool. In totality, staffing of the 25 graduate pharmacology programs in the USA in 2016 and in 2021 were top - heavy experience and expert laden with the professorial cadre, diversified, and depicted dynamism during COVID-19 pandemic.KEY WORDS: academic staff, staff strength, USA universities, Nigerian universities, pharmacology, PhD program.